The Dimensions and Units of the Population Interaction Coefficients - Arditi, Roger; Tyutyunov, Yuri V.; Titova, Lyudmila I.; Rohr, Rudolf P.; Bersier, Louis-Félix (Frontiers in Ecology and Evolution, 2021)
We discuss the interpretation and dimensions of the population dynamic parameters that are commonly used to quantify the strength of intraspecific and interspecific interactions. The concept of “interaction strength” is not univocal. Its theoretical formalization relies on the Generalized Lotka-Volterra model. However, four different ways of parameterizing the model have been proposed in the literature, leading to four different definitions of the term “interaction strength”. In particular, the dimensions of these four definitions are not identical, some of these incorporating explicitly the dimension used to measure the population size. Using an individual-based simulation model as an illustration, we show that, in the latter case, the interaction strength depends implicitly on the habitat size. As a consequence, it is of crucial importance to quantify the population as a density rather than an absolute population abundance. We insist that the dimension of the interaction strength coefficient should not be overlooked and any quantitative estimation must be given with explicit units.